Integration of transcriptome and metabolome analyses reveals key lodging-resistance-related genes and metabolic pathways in maize - Liu, Lei; Liu, Songtao; Lu, Haibo; Tian, Zaimin; Zhao, Haichao; Wei, Dong; Wang, Shuo; Huang, Zhihong (Frontiers in Genetics, 2022)
Stalk lodging, breakage of the stalk at or below the ear, is one of the vital factors causing substantial yield losses in maize (Zea mays. L). Lodging affects maize plants physiological and molecular processes, eventually impacting plant growth and productivity. Despite this known fact, few researchers have investigated the genetic architecture underlying lodging. Herein, therefore, through a comprehensive comparative stem transcriptome, metabolome and phenotypic analysis of three contrasting hybrid lines (high-resistance JNK738, mild-resistance JNK728, low-resistance XY335) at the tasseling stage, we identified key lodging-resistance genes and pathways in maize. Based on the RNA-Seq analysis, a total of 10 093 differentially expressed genes (DEGs) were identified from comparison of three varieties in pairs. The important lodging-resistance metabolism pathways were obtained by KEGG enrichment analysis, the DEGs were predominantly related to phenylpropanoid biosynthesis, and biosynthesis of secondary metabolites enriched In L_vs_H and M_vs_H comparisons. Further, K-means analysis clustered those DEGs into clear and distinct expression profiles at each cultivar. Several functional and regulatory genes involved in cell wall assembly, lignin biosynthetic process, and hormone metabolic process were identified in the special clusters related to lodging-resistance. Subsequently, integrated metabolome and transcriptome analysis revealed that the nine metabolites related to lignin showed different expression trends in the three hybrid cultivars. Among them, L-Phenylalanine and p-Coumaric acid was determined as differentially metabolites (DMs) universal across the three comparisons. These two DMs referred to phenylalanine metabolism and biosynthesis pathways, which were also supplemented by the RNA-Seq data. The plant hormone signal transduction pathway, genes encoding auxin, abscisic acid, jasmonates, and salicylic acid were differentially expressed in the three comparisons of lodging-resistance, indicating these DEGs were valuable potential targets for improving maize lodging resistance. Finally, comparative physiological analysis and qRT-PCR results supported our transcriptome based findings. Our research not only provides a preliminary theoretical basis and experimental ideas for in-depth study of the regulatory networks involved in maize lodging-resistance regulation, but also offers a theoretical basis for opening up a new method for molecular maize lodging-resistance breeding.